Acrylic water-absorbent resin and preparation method thereof

The preparation of acrylic water-absorbent resin by drying using organic solvent extraction has solved the problem of high water-absorbent resin with high respiration, and achieved the effect of low respiration and high suction speed. It is suitable for personal care and cable water barriers.

CN119798517APending Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510002334.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing highly absorbent resin has a higher re-infiltration after absorbing water, resulting in the moisture and extractable part of the gel surface penetration to the non-woven fabric surface, corroding metals and optical fibers, affecting signal transmission.

Method used

The acrylic water-absorbent resin is prepared by drying method of organic solvent extraction to avoid high-temperature drying steps, and water is removed by using hydrophilic solvents to maximize the preservation of bubbles and pores inside the colloid and improve re-seepage performance.

Benefits of technology

It effectively reduces the re-infiltration value of acrylic water-absorbing resin, ensures that moisture can penetrate into the resin quickly, improves the speed of absorption performance, and is suitable for personal care and cable water barriers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225707050000041
    Figure BDA0005225707050000041
  • Figure BDA0005225707050000061
    Figure BDA0005225707050000061
Patent Text Reader

Abstract

The invention provides an acrylic water-absorbent resin and a preparation method thereof. According to the method, gel particles are dried through organic solvent extraction without a high-temperature drying step, the organic solvent and water are mutually soluble, and the boiling point is higher than 100 DEG C under the standard atmospheric pressure. According to the method, water in the colloid is removed at low temperature or normal temperature, bubbles and pore channels in the colloid can be reserved to the maximum extent, and the reverse osmosis performance of the high-molecular water-absorbent resin is guaranteed. The method can be used in the personal care field of baby diapers, adult diapers, sanitary napkins and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical polymer materials, and in particular relates to an acrylic acid water-absorbing resin and a preparation method thereof. Background Art

[0002] Super absorbent resin (SAP) is a water-absorbing material that can absorb hundreds or thousands of times its own weight of pure water. It is difficult to remove water even under pressure. These excellent properties make super absorbent resin widely used in sanitary industries such as diapers and sanitary napkins, as well as industrial and agricultural waterproofing fields such as agricultural and forestry water conservation, construction, and cable water blocking. At present, after the super absorbent resin prepared by high-temperature drying process absorbs water, the colloid expands to form a gel, and some water will remain on the surface of the gel and is difficult to penetrate into the gel. At the same time, the small molecules in the super absorbent resin molecules, that is, the extractable part, will slowly precipitate to the surface of the gel with the water, and it will feel wet after touching, which is called back seepage.

[0003] Taking water-blocking cable as an example, the super absorbent resin is evenly distributed on the non-woven fabric, and after being coated with adhesive, it is curled to form a water-blocking base tape. The water absorption performance of the base tape is mainly determined by the super absorbent resin distributed in it. After the super absorbent resin absorbs water, if the re-permeation is poor, the water and extractable part of the gel surface will penetrate into the surface of the non-woven fabric, and then contact with the cable surface, corroding the metal and optical fiber, causing hydrogen loss, short line, reduced insulation, and affecting signal transmission. Therefore, the re-permeation performance of the super absorbent resin is one of the important indicators affecting its application field.

[0004] At present, the method for improving the back osmosis is mainly to improve the gel strength of the super absorbent resin, improve its gel pressure resistance after absorbing water, and then improve the back osmosis. CN114573745A relates to the preparation of a super absorbent resin with high gel strength, and improves the gel strength by adding nano cellulose during surface treatment. Because nano cellulose has poor compatibility with high molecular water-absorbing resin, during surface treatment, the nano cellulose is mostly on the resin surface and can not be evenly distributed inside the water-absorbing resin, so the improvement of gel strength is limited. And if the amount of nano cellulose added is too much, it will affect the water absorption performance of the water-absorbing resin, causing the water absorption capacity to decline, which is not worth the loss.

[0005] In summary, there are still technical problems of high re-infiltration of super absorbent resin in the fields of personal care, cable water blocking, agriculture and forestry water conservation, etc. The relevant improvement plans cannot take into account the simultaneous improvement of re-infiltration and absorption performance, which seriously affects the downstream application experience. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing an acrylic acid water-absorbent resin, which adopts a drying method of organic solvent extraction and can effectively solve the problem of high back seepage.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing an acrylic water-absorbing resin, wherein the drying method of gel particles adopts organic solvent extraction without a high-temperature drying step; the organic solvent is miscible with water and has a boiling point higher than 100° C. under standard atmospheric pressure.

[0009] The inventors have found that during the exothermic polymerization process of the super absorbent resin, a large number of bubbles and pores will be generated inside the colloid. During high-temperature drying, as the water evaporates, the polymer network collapses, a large number of bubbles disappear, and the pores are closed. After absorbing water, a large amount of water in the obtained super absorbent resin particles remains on the surface of the particles and cannot quickly penetrate into the interior of the particles, resulting in high back osmosis, which affects the use effect. By extracting and removing water with a hydrophilic solvent, the water in the colloid can be removed at low or normal temperatures. And the bubbles and pores inside the colloid can be retained to the maximum extent, ensuring the back osmosis performance of the polymer absorbent resin.

[0010] In one embodiment of the present invention, the organic solvent is selected from C2-C4 alcohol solvents with a boiling point above 100°C at normal pressure, preferably one or more of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and glycerol, more preferably 1,2-propylene glycol.

[0011] In one embodiment of the present invention, the preparation method comprises the following steps:

[0012] S1: mixing acrylic acid with alkali solution, a cross-linking agent and water to obtain a polymerizable monomer composition;

[0013] S2: adding an initiator to the polymerization monomer composition to obtain a polymer colloid, and granulating to obtain gel particles;

[0014] S3: After the gel particles are extracted with an organic solvent, the organic solvent is removed and dried to obtain a primary acrylic water-absorbing resin;

[0015] S4: performing secondary cross-linking on the primary acrylic water-absorbing resin using a surface cross-linking agent to obtain the desired acrylic water-absorbing resin.

[0016] In one embodiment of the present invention, the crosslinking agent in S1 is selected from acrylates and / or ethers containing carbon-carbon double bonds, preferably one or more of polyethylene glycol diacrylate, pentaerythritol diallyl ether, pentaerythritol triallyl ether, polyethylene glycol diallyl ether, pentaerythritol diacrylate, pentaerythritol triacrylate, glycerol triacrylate, ethoxylated glycerol triallyl ether, trimethylolpropane triacrylate, more preferably pentaerythritol triallyl ether; preferably, the amount of the crosslinking agent added is 0.1%-0.8% of the mass of acrylic acid. The above crosslinking agents and their amounts are well known in the art, and similar technical effects can be obtained by using other similar materials.

[0017] In one embodiment of the present invention, the initiator S2 is a thermal initiator, preferably one or more of sodium persulfate, potassium persulfate, ammonium persulfate, 2'2-azo[2-methyl-N-(2-hydroxyethyl)propionamide], azobisisobutylimidazoline and 2'2-azo-bis(2-methyl)propylamidine dihydrochloride, more preferably sodium persulfate and / or potassium persulfate; preferably, the initiator is added in an amount of 0.03-0.3wt% of the mass of acrylic acid. The above initiators and their amounts are well known in the art, and similar technical effects can be obtained by using other similar materials.

[0018] In one embodiment of the present invention, the water content of the gel particles after S3 extraction is less than 2%.

[0019] In the present invention, S3 can remove the organic solvent by common methods such as filtration and centrifugation. The entire drying process can be carried out at room temperature, and no chemical reaction occurs between the organic solvent and the polymer resin. After drying, it is ground and sieved by a grinder to obtain a primary acrylic water-absorbing resin. The above-mentioned processes for removing organic solvents are all common chemical processes.

[0020] In one embodiment of the present invention, the surface crosslinking agent in S4 comprises one or more of water, polyols, epoxy compounds, and metal salt inorganic compounds; wherein the polyol preferably comprises one or more of ethylene glycol, propylene glycol, glycerol, diethylene glycol, 1,4-butanediol, pentanediol, and polyvinyl alcohol; wherein the epoxy compound preferably comprises one or more of ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, ethylene carbonate, and propylene carbonate; wherein the metal salt inorganic compound preferably comprises one or more of kaolin, alumina, sodium sulfate, magnesium sulfate, aluminum sulfate, magnesium chloride, calcium chloride, aluminum chloride, and zinc chloride; preferably, the surface crosslinking agent is ethylene glycol diglycidyl ether: aluminum sulfate: ethylene glycol: water mass ratio = (2-4): (7-9): (17-19): (49-51); preferably, the amount of the surface crosslinking agent is 2-8wt% of the mass of the primary acrylic water-absorbing resin. The above-mentioned polyols, epoxy compounds, metal salt inorganic compounds and their usage are well known in the art, and similar technical effects can be obtained by using other similar materials.

[0021] Another object of the present invention is to provide an acrylic water-absorbent resin.

[0022] An acrylic water-absorbing resin is prepared by the above-mentioned preparation method, and the resin has a re-osmosis value of ≤0.8g.

[0023] Another object of the present invention is to provide a use of an acrylic water-absorbent resin.

[0024] A use of an acrylic water-absorbent resin, wherein the resin is prepared by the above preparation method or is the above resin, and the resin is used in the field of personal care, preferably in baby diapers, adult diapers, and sanitary napkins.

[0025] Compared with the prior art, the present invention has the following positive effects:

[0026] The acrylic water-absorbing resin prepared by the present invention has a special hollow structure, has strong water absorption and water retention capabilities, and has a low reverse osmosis of ≤0.8g, and is suitable for personal care industries such as baby diapers and adult diapers. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0028] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0029] Acrylic acid: Wanhua Chemical Group Co., Ltd., industrial products;

[0030] 32%wt sodium hydroxide solution: Wanhua Chemical Group Co., Ltd., industrial product;

[0031] Pentaerythritol triallyl ether, glycerol triacrylate: Japan DAISO Co., Ltd., industrial products;

[0032] Sodium persulfate, potassium persulfate: Hebei Yatai Electrochemical Co., Ltd., industrial products;

[0033] Ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether: Japan Nagase Chemical, brand DENACOL EX-810;

[0034] Aluminum sulfate, magnesium chloride: Zibo Yiheng Environmental Protection Materials Co., Ltd., industrial products;

[0035] Ethanol: industrial product;

[0036] Ethylene glycol, 1,4-butanediol: industrial products;

[0037] 1,2-Propanediol: industrial product;

[0038] The performance of super absorbent resin products is tested according to the following analysis methods:

[0039] (1) Reverse osmosis evaluation

[0040] The test method is as follows: add 2g of super absorbent resin to 50g of normal saline, place it in a ziplock bag and shake it evenly. After one hour, spread the gel on a surface dish with a diameter of 12cm, place 20 pieces of 11cm qualitative filter paper, and record the mass as m1. Press with a 500g weight for 30 minutes, and weigh the mass of the filter paper as m2. The reverse osmosis amount is m2-m1, in grams, and the index range is ≤0.8.

[0041] (2) Other performance test standards

[0042]

[0043] Example 1

[0044] 1868 g of acrylic acid, 2432 g of 32 wt% sodium hydroxide solution, 940 g of water, and 3.8 g of pentaerythritol triallyl ether were added to a reaction kettle, and mixed to obtain a neutralized solution.

[0045] The temperature of the neutralization solution was controlled at 90°C, and 65g of a 2wt% sodium persulfate aqueous solution was added to the neutralization solution, and then the uniformly mixed neutralization solution was poured into a polymerization tank. The polymerization tank was placed in an oven at 80°C, and after reacting for 6 minutes, a polymer hydrogel was obtained, which was granulated by a granulator, and the gel particle size was between 1-10mm.

[0046] Take 1000g of gel particles, mix and stir with 50Kg of 1,2-propylene glycol, and filter and centrifuge after 30min. After repeating 3 times, the water content of the gel particles is measured to be 1.5%. After grinding and sieving by rollers, primary acrylic acid absorbent resin powder with a particle size of 155μm is obtained. Take 500g of primary acrylic acid absorbent resin powder, spray 35g of surface crosslinking agent evenly on the surface, and the surface crosslinking agent is prepared according to the mass ratio of ethylene glycol diglycidyl ether: aluminum sulfate: ethylene glycol: water = 3:8:18:50, and finally put it into an oven at 140°C to dry for 50min, and obtain a 168μm high absorbent resin product after sieving.

[0047] The properties of super absorbent resin products are shown in Table 1.

[0048] Example 2

[0049] 1868 g of acrylic acid, 2432 g of 32 wt% sodium hydroxide solution, 940 g of water, and 13 g of pentaerythritol triallyl ether were added to a reaction kettle, and mixed to obtain a neutralized solution.

[0050] The temperature of the neutralization solution was controlled at 90°C, and 65g of a 7.2wt% sodium persulfate aqueous solution was added to the neutralization solution, and then the uniformly mixed neutralization solution was poured into a polymerization tank. The polymerization tank was placed in an oven at 80°C, and after reacting for 6 minutes, a polymer hydrogel was obtained, which was granulated by a granulator, and the gel particle size was between 2-10mm.

[0051] Take 1000g of gel particles, mix and stir with 50Kg of ethylene glycol, and filter and centrifuge after 30min. After repeated 2 times, the water content of the gel particles is measured to be 1.7%. After grinding and sieving by rollers, primary acrylic acid water-absorbing resin powder is obtained, and the particle size is 160μm. Take 500g of primary acrylic acid water-absorbing resin powder, and evenly spray 10g of surface crosslinking agent on the surface. The surface crosslinking agent is prepared according to the mass ratio of ethylene glycol diglycidyl ether: aluminum sulfate: ethylene glycol: water = 3:8:18:50, and finally put it into an oven at 140°C and dry for 50min. After sieving, a highly absorbent resin product of 175μm is obtained.

[0052] The properties of super absorbent resin products are shown in Table 1.

[0053] Example 3

[0054] 1868 g of acrylic acid, 2432 g of 32 wt% sodium hydroxide solution, 940 g of water, and 7.5 g of glycerol triacrylate were added to a reaction kettle, and mixed to obtain a neutralized solution.

[0055] The temperature of the neutralization solution was controlled at 90°C, and 65g of a 4.3wt% potassium persulfate aqueous solution was added to the neutralization solution, and then the mixed neutralization solution was poured into a polymerization tank. The polymerization tank was placed in an oven at 80°C, and the polymer hydrogel was obtained after reacting for 6 minutes. The gel particles were granulated by a granulator, and the size of the gel particles was between 1-9mm.

[0056] Take 1000g of gel particles, mix and stir with 50kg of 1,3-propylene glycol, and filter and centrifuge after 30min. After repeating 3 times, the water content of the gel particles is measured to be 1.8%. After grinding and sieving by rollers, primary acrylic acid absorbent resin powder with a particle size of 157μm is obtained. Take 500g of primary acrylic acid absorbent resin powder, spray 25g of surface crosslinking agent evenly on the surface, and the surface crosslinking agent is prepared according to the mass ratio of propylene glycol diglycidyl ether: magnesium chloride: 1,4-butanediol: water = 2:7:17:49, and finally put it into an oven at 140°C to dry for 50min, and obtain a 172μm high absorbent resin product after sieving.

[0057] The properties of super absorbent resin products are shown in Table 1.

[0058] Comparative Example 1

[0059] Compared with Example 1, the only difference is that the gel particles are dried at high temperature.

[0060] Take 1000g of the gel particles in Example 1 and place them in an oven at 230°C for high temperature drying for 30min. The water content of the gel particles is measured to be 1.5%. After grinding and sieving by a roller method, a primary acrylic acid water-absorbing resin powder is obtained, and the particle size is between 157μm. Take 500g of the primary acrylic acid water-absorbing resin powder, and evenly spray 35g of a surface crosslinking agent on the surface. The surface crosslinking agent is prepared according to the mass ratio of ethylene glycol diglycidyl ether: aluminum sulfate: ethylene glycol: water = 3:8:18:50, and finally put it into an oven at 140°C for drying for 50min. After sieving, a highly absorbent resin product of 174μm is obtained.

[0061] The properties of super absorbent resin products are shown in Table 1.

[0062] Comparative Example 2

[0063] Compared with Example 2, the only difference is that the gel particles are extracted with ethanol.

[0064] Take 1000g of the gel particles in Example 2, mix with 50Kg of ethanol, and filter and centrifuge after 30min. After repeating 3 times, the water content of the gel particles is measured to be 1.9%. After grinding and screening, a primary acrylic acid water-absorbing resin powder with a particle size of 166μm is obtained. Take 500g of the primary acrylic acid water-absorbing resin powder, spray 10g of surface crosslinking agent evenly on the surface, the surface crosslinking agent is prepared according to the mass ratio of ethylene glycol diglycidyl ether: aluminum sulfate: ethylene glycol: water = 3:8:18:50, and finally put it into an oven at 140°C and dry it for 50min. After grinding and screening, a highly absorbent resin product of 177μm is obtained.

[0065] The properties of super absorbent resin products are shown in Table 1.

[0066]

[0067] As can be seen from Table 1, in Comparative Example 1, the gel particles are dehydrated by conventional high-temperature drying. During the high-temperature dehydration process, the polymer network gradually collapses, the bubbles disappear, and the pores are closed. After absorbing water, a large amount of water remains on the surface of the particles, and cannot quickly penetrate into the interior of the particles, resulting in a high back-infiltration rate. At the same time, due to the change in specific surface area, the absorption rate is slow. In Example 1 / 2, the gel particles are dehydrated by hydrophilic solvent extraction, and the bubbles and pores in the polymer network are retained to the maximum extent. After the super absorbent resin particles absorb water, the water can quickly penetrate into the interior of the polymer network through the bubbles and pores, and the water remaining on the surface is small, and the back-infiltration is low. At the same time, due to the presence of bubbles and pores inside the polymer network, the absorption rate of the polymer absorbent resin is faster. In Comparative Example 2, ethanol extraction and water removal were adopted, and the performance of the obtained product was between that of Comparative Example 1 and that of the embodiment. This was because ethanol had a small molecular weight and its affinity with the polymer water-absorbing resin was between that of water and ethylene glycol / 1,2-propylene glycol. Some ethanol molecules remained inside the polymer network, blocking bubbles and pores instead, and the overall improvement effect was not as good as that of the embodiment.

[0068] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for preparing an acrylic acid water-absorbent resin, characterized in that: In the preparation method, the drying method of the gel particles is organic solvent extraction, without a high-temperature drying step; The organic solvent is miscible with water and has a boiling point higher than 100° C. under standard atmospheric pressure.

2. The preparation method according to claim 1, characterized in that: The organic solvent is selected from C2-C4 alcohol solvents, with a boiling point above 100° C. at normal pressure, preferably one or more of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and glycerol, and more preferably 1,2-propylene glycol.

3. The preparation method according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1: mixing acrylic acid with alkali solution, a cross-linking agent and water to obtain a polymerizable monomer composition; S2: adding an initiator to the polymerization monomer composition to obtain a polymer colloid, and granulating to obtain gel particles; S3: After the gel particles are extracted with an organic solvent, the organic solvent is removed and dried to obtain a primary acrylic water-absorbing resin; S4: performing secondary cross-linking on the primary acrylic water-absorbing resin using a surface cross-linking agent to obtain the desired acrylic water-absorbing resin.

4. The preparation method according to claim 3, characterized in that: S1 The crosslinking agent is selected from acrylates and / or ethers containing carbon-carbon double bonds, preferably one or more of polyethylene glycol diacrylate, pentaerythritol diallyl ether, pentaerythritol triallyl ether, polyethylene glycol diallyl ether, pentaerythritol diacrylate, pentaerythritol triacrylate, glycerol triacrylate, ethoxylated glycerol triallyl ether, trimethylolpropane triacrylate, more preferably pentaerythritol triallyl ether; Preferably, the amount of the cross-linking agent added is 0.1%-0.8% of the mass of acrylic acid.

5. The preparation method according to claim 3, characterized in that: S2 The initiator is a thermal initiator, preferably one or more of sodium persulfate, potassium persulfate, ammonium persulfate, 2'2-azo[2-methyl-N-(2-hydroxyethyl)propionamide], azobisisobutylimidazoline and 2'2-azo-bis(2-methyl)propylamidine dihydrochloride, more preferably sodium persulfate and / or potassium persulfate; Preferably, the initiator is added in an amount of 0.03-0.3 wt % of the mass of acrylic acid.

6. The preparation method according to claim 3, characterized in that: The water content of the gel particles after S3 extraction was less than 2%.

7. The preparation method according to claim 3, characterized in that: S4: The surface crosslinking agent comprises one or more of water, polyol, epoxy compound, and metal salt inorganic compound; Wherein, the polyol preferably comprises one or more of ethylene glycol, propylene glycol, glycerol, diethylene glycol, 1,4-butanediol, pentanediol, and polyvinyl alcohol; Wherein, the epoxy compound preferably comprises one or more of ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, ethylene carbonate, and propylene carbonate; Wherein, the metal salt inorganic compound preferably comprises one or more of kaolin, alumina, sodium sulfate, magnesium sulfate, aluminum sulfate, magnesium chloride, calcium chloride, aluminum chloride, and zinc chloride; Preferably, the surface crosslinking agent is ethylene glycol diglycidyl ether: aluminum sulfate: ethylene glycol: water mass ratio = (2-4): (7-9): (17-19): (49-51); Preferably, the surface crosslinking agent is used in an amount of 2-8 wt % of the mass of the primary acrylic water-absorbing resin.

8. An acrylic water-absorbent resin, which is prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The resin re-permeation value is ≤0.8g.

9. Use of an acrylic water-absorbent resin, wherein the resin is prepared by the preparation method according to any one of claims 1 to 7, or is the resin according to claim 8, and the resin is used in the field of personal care, preferably in baby diapers, adult diapers, and sanitary napkins.

Citation Information

Patent Citations

  • Water-absorbing resin and preparing method thereof

    CN105837726A

  • Absorbent polymer and method of preparing the same

    CN105837728A

  • Preparation method of double-crosslinking high-water-absorbability resin

    CN109810215A

  • High-performance acrylic water-absorbent resin and preparation method thereof

    CN113943433A

  • Acrylic water-absorbent resin and preparation method thereof

    CN117069972A